Performance analysis of solar collectors with varying glass thickness for water heaters - Panjaitan, Abryan Termedia; Sianturi, Tambos August; Siahaan, Azarya NJ (Lembaga Riset Mutiara Akbar, 2026)
The increasing global energy demand encourages the use of renewable energy, especially solar energy which has great potential in tropical regions such as Indonesia. This study aims to analyze the performance of flat plate solar collectors with variations in local glass thickness (3 mm and 5 mm) for household water heating systems. The method used is a field experiment with measurements of water temperature parameters (?T), heat transfer rate (Qout), absorbed heat energy (Qin), and solar radiation energy (Qs) in the time range of 11:00–14:00 WIB. The results show that 3 mm glass produces higher outlet water temperatures and heat transfer rates due to better radiation transmission capabilities, especially at low intensities. However, 5 mm glass has a higher and more stable thermal efficiency, with a maximum value reaching 71%, due to better insulation capabilities in suppressing heat loss. Overall, glass thickness has a significant effect on solar collector performance. Therefore, local glass with a thickness of 5 mm is recommended to increase the efficiency of solar energy-based water heating systems that are economical and environmentally friendly.